2019
DOI: 10.2174/1570159x16666180302120322
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria: A Connecting Link in the Major Depressive Disorder Jigsaw

Abstract: Mitochondria are integral to the function of neurons and undergo dysfunction in major depressive disorder patients. This dysfunction is reflected in all the various hypotheses that have been proposed for depression. Among the newer targets identified, which also involve mitochondria, includes the role of exogenous ATP. The diversity of purinergic receptors, and their differential expression among various individuals in the population, due to genetic and environmental (prenatal) influences, may influence the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 232 publications
(151 reference statements)
1
40
0
Order By: Relevance
“…These findings strongly support critical roles of oxidative stress in the pathologies of AD, PD, and depression. Due to its direct relationship with oxidative stress, mitochondrial dysfunction also plays a key role in the pathogenesis of AD [ 63 ], PD [ 64 ], and depression [ 61 , 65 ]. Meanwhile, neurotrophic factors such as glial cell-derived neurotrophic factor, nerve growth factor, and especially, BDNF are crucial for survival, maintenance, and regeneration of specific neurons in the adult brain [ 66 ].…”
Section: Major Pathologies and Therapeutic Strategies Of Ad Pd Amentioning
confidence: 99%
“…These findings strongly support critical roles of oxidative stress in the pathologies of AD, PD, and depression. Due to its direct relationship with oxidative stress, mitochondrial dysfunction also plays a key role in the pathogenesis of AD [ 63 ], PD [ 64 ], and depression [ 61 , 65 ]. Meanwhile, neurotrophic factors such as glial cell-derived neurotrophic factor, nerve growth factor, and especially, BDNF are crucial for survival, maintenance, and regeneration of specific neurons in the adult brain [ 66 ].…”
Section: Major Pathologies and Therapeutic Strategies Of Ad Pd Amentioning
confidence: 99%
“…In addition, alterations in dopamine neurotransmission in the reward circuitry were also disrupted by a high-fat diet, inducing depressive-like behavior in mice through mediation of impaired brain insulin signaling [26]. The suggested mechanisms that mediate insulin signaling and dopaminergic neurotransmission, including mitochondrial dysfunction [95][96][97], oxidative stress [98][99][100], impaired leptin [101,102] and purinergic signaling [103], and disrupted dopaminergic neurotransmission [104], are known to play important roles in the pathophysiology of depression.…”
Section: Brain Insulin Resistancementioning
confidence: 99%
“…68 Chronic central administration of IL-1β in rats caused depressive-like symptoms. 22 On the other hand, inflammation has been well demonstrated to cause mitochondrial dysfunction. 70 In stressed rats, intracerebral infusion of RNAi against IL-1β ameliorated neuronal apoptosis and depression-like behaviors.…”
Section: Mitochondria In Depressionmentioning
confidence: 99%
“…A recent study revealed that exogenous ATP released from damaged mitochondria can activate purinergic receptor to promote inflammation. 22 On the other hand, inflammation has been well demonstrated to cause mitochondrial dysfunction. In patients with sepsis, various indicators of mitochondrial function were decreased.…”
Section: Mitochondria In Depressionmentioning
confidence: 99%
See 1 more Smart Citation